Synthesis of Fe Ionic-Imprinted Polyeugenol Using Polyethylene Glycol Diglycidilether as Cross-Linking Agent for Sorption of Fe(III) - Muhammad Cholid Djunaidi; Jumina Jumina; Dwi Siswanta; Mathias Ulbricht (Indonesian Journal of Chemistry, 2015)
Fe-Ionic Imprinted Polymer (IIP) from polyeugenol as base polymer and polyethylene glycol diglycidyl ether (PEGDE) as cross-linking agent had been synthesized to adsorb Fe(III) from aqueous media. The non-imprinting material (NIP) and polyeugenol were used in the adsorption study as control. Synthesis work included polymerization, template uploading, crosslinking and template removal, optimized for different template ion upload pH and concentrations. The polymers were characterized by FTIR spectroscopy, XRD and SEM-EDX, followed by adsorption test to study the adsorption kinetics and isotherms for all adsorbents. Selective adsorption study of IIP was carried out using binary mixtures of Fe(III) and Cr(III), Pb(II), Cd(II). Experimental results showed that the optimum conditions for the synthesis was template upload pH of 3, Fe/polyeugenol ratio of 1 mg/g, while the optimum adsorption pH was 3. The adsorption mechanism of Fe(III) on all adsorbents was dominated by hydrogen bond formation. The adsorption kinetics followed the pseudo-second-order model while the equilibrium data was best explained by the Langmuir isotherm model. The adsorption capacity of Fe(III) on the IIP was 12.73 mg/g, higher than that of the other adsorbents. Results also show that IIP-Fe was more selective toward Fe than NIP by 2.69 (Cd), 1.66 (Cr) and 1.6 (Pb) fold, respectively.